2018
DOI: 10.1002/jms.4311
|View full text |Cite
|
Sign up to set email alerts
|

Energetic switch of the proline effect in collision‐induced dissociation of singly and doubly protonated peptide Ala‐Ala‐Arg‐Pro‐Ala‐Ala

Abstract: Suppression of the selective cleavage at N‐terminal of proline is observed in the peptide cleavage by proteolytic enzyme trypsin and in the fragment ion mass spectra of peptides containing Arg‐Pro sequence. An insight into the fragmentation mechanism of the influence of arginine residue on the proline effect can help in prediction of mass spectra and in protein structure analysis. In this work, collision‐induced dissociation spectra of singly and doubly charged peptide AARPAA were studied by ESI MS/MS and theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Because of its unique properties, proline often leads to missed proteolytic events during digestion [9], increasing the resultant peptide length and database search complexity. Moreover, proline also effects the fragmentation step during mass analysis, known as the 'proline effect' [20], where fragmentation shows enhanced production of y-ions spanning from the proline to the peptide C terminus due to the enhanced basicity of the proline nitrogen, restricting the peptide sequence coverage [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its unique properties, proline often leads to missed proteolytic events during digestion [9], increasing the resultant peptide length and database search complexity. Moreover, proline also effects the fragmentation step during mass analysis, known as the 'proline effect' [20], where fragmentation shows enhanced production of y-ions spanning from the proline to the peptide C terminus due to the enhanced basicity of the proline nitrogen, restricting the peptide sequence coverage [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…S1 in ESI. † The structure with the lowest energy was selected to perform a geometric optimization and to search reaction pathways 18 at the B3LYP/def-TZVP level using Turbomole supported by ChemShell 3.7.0. 34 Key transition states with only one imaginary frequency were further validated by intrinsic reaction coordinate (IRC) calculations to confirm their connections.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…16 Several studies have suggested that the oxazolone structure is likely a b 2 isomer. [17][18][19][20] Moreover, the possibility for an isomerization between an oxazolone and a diketopiperazine form has been exploited. 21 In the diketopiperazine pathway, the N-terminal amino group acts as a nucleophile and attacks the carbonyl carbon of the second amino acid residue, forming a more stable six-membered ring structure (Path c in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%